Rising Caesarean Section Rates: An Audit of Caesarean Sections in a Specialist Private Practice - Riona P. Naidoo; Jagidesa Moodley (South African Family Practice)
Background: Caesarean section (CS) rates are increasing worldwide; rates in the private sector in South Africa are reported to be particularly high. To the best of our knowledge there has been no recent audit of Caesarean sections performed by the private health sector in KwaZulu-Natal. The aim of this study was to carry out an audit of CS in a private practice.